Reimagining Christianity : - Jones, Alan W. (John Wiley & Sons, 2005)
Religious faith, Jones says, shouldn't be so much a refuge from the realities of the world as a launching pad for our imaginations. The dean of San Francisco's Grace (Episcopal) Cathedral begins by wondering whether there is a future for faith and concludes that there is, but that faith could be much more meaningful to a greater number of people if religion would shed its adherences to exclusionary, tribal attitudes and strict, dogmatic thinking. Focusing on Christianity, but hurling bouquets and brickbats at all the major religions, Jones doesn't demonize organized religion, nor does he stand up as its loudest cheerleader. Targeting primarily lapsed Catholics, atheists, and the simply lost, he abstracts their by now extremely familiar stories of religion gone bad and actually draws strength for his thesis from such straying believers' damaged faith. No complainer, he proposes ways to reimagine Christianity by embracing those who think differently and releasing notions of dogma as containing the answers to all the questions now and forevermore.